Teaching comprehension strategies through the use of puppets and sensory experiences - Johnson, Sarah (My University, 2014)
Comprehending while reading is an important skill for making meaning. Learning how to comprehend and think about books, while decoding words, is a very demanding task. Many children in the primary grades are so focused on decoding words that they aren't thinking about what they are reading. The purpose of this study was to see how exposure to comprehension puppets and sensory experiences, through whole and small group lessons, would affect students' ability to think about what is being read and retell stories. Would their listening comprehension scores increase? Would their reading comprehension scores increase on the F&P Assessment? The comprehension puppets were used 1-2 times a week during read-alouds, guided reading, and during the mini-lesson prior to independent reading. A pre and post attitude survey, listening comprehension assessments, and F&P Assessments were used to determine if students demonstrated growth in understanding comprehension skills. Research did show that the use of comprehension puppets and sensory experiences increased students listening comprehension.
Plan B Paper. 2014. Master of Science in Education- Reading--University of Wisconsin-River Falls. Teacher Education Department. 42 leaves. Includes bibliographical references (leaves 41-42).